Aproximación al poblamiento tardorromano en el norte del municipio de Lorca - Martínez Rodríguez, Andrés (Antigüedad y Cristianismo, 1998)
A catalogue of the archaeological sites up to now in the northern district of Lorca. Each one is studied but only in so far as was posible given the materials found in the survey. Some reflections are offered on late antiquity and its archaeology .